2014
DOI: 10.1016/j.geoderma.2013.12.029
|View full text |Cite
|
Sign up to set email alerts
|

Carbon storage and soil organic matter stabilisation in near-natural, restored and embanked Swiss floodplains

Abstract: Over recent decades, the number of floodplain restoration projects has increased worldwide. In Switzerland, several projects have been implemented to maintain or recreate ecological functions of floodplains. Despite this, little is known about the potential of floodplain soils to release and/or accumulate carbon. In alluvial soils, carbon storage is strongly influenced by fluvial dynamics, and therefore a better understanding of carbon fluxes and stocks in such settings is clearly needed. To evaluate the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…This result revealed that the SOCD showed a significantly positive correlation with the silt and clay contents and a significantly negative correlation with the sand content, which is similar to the results reported for riparian areas in other regions (Bechtold and Naiman 2006;Bullinger-Weber et al 2014). The main reason for this is that fine fractions (clay and silt) can retain more soil organic matter than coarser fractions (Dai et al 2011;Ruiz-Sinoga et al 2012).…”
Section: Influence Of Soil Texture On the Socdsupporting
confidence: 86%
See 2 more Smart Citations
“…This result revealed that the SOCD showed a significantly positive correlation with the silt and clay contents and a significantly negative correlation with the sand content, which is similar to the results reported for riparian areas in other regions (Bechtold and Naiman 2006;Bullinger-Weber et al 2014). The main reason for this is that fine fractions (clay and silt) can retain more soil organic matter than coarser fractions (Dai et al 2011;Ruiz-Sinoga et al 2012).…”
Section: Influence Of Soil Texture On the Socdsupporting
confidence: 86%
“…This result is related to the influence of flooding, sedimentation, riparian vegetation and human activities (Ricker et al 2013). In the frequently flooded zone, frequent floods and the concomitant deposition of carbon-rich sediments (deposition amount [ erosion amount) usually lead to an increase in soil organic carbon stocks (Cierjacks et al 2010b;Bullinger-Weber et al 2014). The study of Cabezas and Comín (2010) on organic carbon accretion rates after individual flooding events in a reach on the Middle Ebro River in Spain revealed that dry flood deposits in the riparian area ranged from 2330.70 to 5987.41 g/m 2 , and the total organic carbon accretion rate ranged from 58.97 to 70.59 g/m 2 .…”
Section: Changes In Socd In the Riparian Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The pioneer habitat in which the freeze-cores were extracted is characterized by an herbaceous vegetation (Phalaris arundinacea). A high sand content (86 ± 16% of the mineral phase) and a low proportion of organic carbon (1.5 ± 0.5% of the total soil) have been measured (Bullinger-Weber et al, 2014). The freeze-core sampling technique used in this study is similar to the one described in detailed in Humpesch and Niederreiter (1993).…”
Section: Overview Of the Experimental Designmentioning
confidence: 99%
“…The freeze-cores were extracted in the largest restored floodplain of Switzerland, the "Schäffäuli" protected area (47°35′27.93″N, 8°46′21.33″E) located along the Thur River in North-East Switzerland and largely described in several previous studies (Bullinger-Weber et al, 2014;Fournier et al, 2012;Schirmer et al, 2014;Schneider et al, 2011). The pioneer habitat in which the freeze-cores were extracted is characterized by an herbaceous vegetation (Phalaris arundinacea).…”
Section: Overview Of the Experimental Designmentioning
confidence: 99%